A novel κ-carrageenan/konjac gum thermo-irreversible gel improved by gellan gum and Ca2+. (15th January 2022) - Cui, Bing; Chen, Wenxin; Liang, Hongshan; Li, Jing; Wu, Di; Ye, Shuxin; Li, Bin
Abstract: The thermal stability of the κ-carrageenan/konjac gum (KC/KGM) mixed gel during heating treatment (at 85 °C for 30 min) does not satisfy the demand of the practical application. To solve this problem, gellan gum (GG) or/and Ca 2+ were introduced in the κ-carrageenan/konjac gum (KC/KGM) mixed system to enhance mechanical and thermal properties. The effect of GG and Ca 2+ on the gel matrix properties was studied by two deformation test (TDT), rheological measurement, scanning electron microscopy (SEM), combined with visual observation. The results showed that neither GG nor Ca 2+ alone could reduce the deterioration of the mechanical properties of the KC/KGM gel after heat treatment (at 85 °C for 30 min). Only the participation of GG and Ca 2+ could ensure the consistent mechanical properties of the mixed gel before and after heating. The rheological and micro-rheological analysis confirmed that the KC/KGM gel with GG and Ca 2+ could always remain solid-state without gel-sol transition under heat treatment. In addition, the thermo-irreversible gels with different texture properties were prepared by adjusting the mass ratio of KC and KGM. Hence, this study may enrich the design of novel gel-based food ingredients. Highlights: Either Ca 2+ or GG raised the Tgs and Tsg of KC/KGM gels. An amount of Ca 2+ and GG transformed KC/KGM gels into thermo-irreversible gels. The mass ratio of KC and KGM influenced the texture of thermo-irreversible gels. This study provided a gel food ingredient with heat resistant treatment.